2017
DOI: 10.5194/bg-14-2469-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sequential nutrient uptake as a potential mechanism for phytoplankton to maintain high primary productivity and balanced nutrient stoichiometry

Abstract: Abstract. We hypothesize that phytoplankton have the sequential nutrient uptake strategy to maintain nutrient stoichiometry and high primary productivity in the water column. According to this hypothesis, phytoplankton take up the most limiting nutrient first until depletion, continue to draw down non-limiting nutrients and then take up the most limiting nutrient rapidly when it is available. These processes would result in the variation of ambient nutrient ratios in the water column around the Redfield ratio.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…However, Figure e,f shows that Euglenophyta distribution largely favoured Si/P ( P < .05) and Si/DIN ( P < .05) in both the Gan River and Poyang Lake, confirming that influencing phytoplankton community nutrient ratios (Si/P, N/P, and Si/N) are diverse. Liu et al () and Yin et al () also indicated that Si/N was the limiting factor for phytoplankton growth.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, Figure e,f shows that Euglenophyta distribution largely favoured Si/P ( P < .05) and Si/DIN ( P < .05) in both the Gan River and Poyang Lake, confirming that influencing phytoplankton community nutrient ratios (Si/P, N/P, and Si/N) are diverse. Liu et al () and Yin et al () also indicated that Si/N was the limiting factor for phytoplankton growth.…”
Section: Discussionmentioning
confidence: 94%
“…Primary production, which represents phytoplankton biomass and growth rates (Wang et al, ), is sensitive to environmental change (Wu, He, et al, ). It is mainly regulated by various factors that include incident irradiance (Lewis, ; Wang et al, ), ice cover (Lewis, ), nonalgal light attenuation (Deng et al, ; Wu, Lai, Zhang, Cai, & Chen, ), mixing depth (Wu et al, ), temperature (Liang et al, ), and the nutrient supply (Browning et al, ; Dou, Tang, Yang, & Wang, ; Hagstrom & Levin, ; Ke, Tan, Ma, Huang, & Wang, ; Li, Ge, Wang, Zhou, & Hu, ; Liu et al, ; Wang et al, ; Wilkerson, Dugdale, Parker, Blaser, & Pimenta, ; Yin, Liu, & Harrison, ), especially for nutrient inputs that have a significant effect on phytoplankton growth and development as well as the biogeochemical cycles of watersheds (Browning et al, ; Li et al, ; Moore et al, ; Wen et al, ). In addition, nutrient inputs, particularly nitrogen (N) and phosphorus (P), to freshwater ecosystems have continued to increase due to progressively increasing anthropogenic activities resulting from rising populations, broadening economic development, and the greater demand for food and energy production in recent years (Cao, Wang, Liao, Sun, & Huang, ; Wilkerson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many nutrients are released during cell lysis, nitrogen typically limits phytoplankton growth in coastal BC waters (e.g. Yin et al, 2017), the location of the current study. High rates of bacterial mortality from viral lysis imply a continuous and substantial flux of DOM from cells into seawater.…”
Section: Introductionmentioning
confidence: 99%